Comparative Effects of Chlorhexidine, Sodium Hypochlorite, and Ethylene Diamine Tetra-Acetic Acid as Root Canal Irrigants on Pushout Bond Strength of Resil Experimental Sealer and AH26 to Root Dentin - Saeede Zadsirjan; Hengameh Ashraf; Mahshid Kosari; Mostafa Alizadetalarposhti; Sepideh Salimnezhad (Mashhad University of Medical Sciences, 2022)
Introduction: We compared the effects of chlorhexidine (CHX), sodium hypochlorite (NaOCl), and ethylene diamine tetra-acetic acid (EDTA) root canal irrigants on the pushout bond strength of Resil experimental sealer and AH26 to root dentin. Methods: In this in vitro study, 65 teeth were assigned to six groups based on the choice of final irrigant and sealer: (I) CHX and AH26, (II) CHX and Resil, (III) NaOCl and AH26, (IV) NaOCl and Resil, (V) NaOCl plus EDTA and AH26, and (VI) NaOCl plus EDTA and Resil. The teeth were decoronated and underwent chemomechanical preparation. In each group, half of the root canals were filled with AH26 and the other half with Resil plus gutta-percha by the lateral compaction technique. In the control group, the root canals were rinsed with saline and obturated without sealer. The roots were sectioned perpendicular to the longitudinal tooth axis at 3, 7, and 11 mm from the apex (apical, middle, and coronal thirds). The pushout bond strength of sealer to root dentin was measured by a universal testing machine and recorded in Newtons (N). Results: AH26 plus CHX, as well as AH26 plus NaOCl and EDTA, yielded the maximum pushout bond strength (P<0.05). The pushout bond strength in the apical third was higher than that in the middle and coronal thirds. The mean pushout bond strength of both sealers in NaOCl irrigation groups was lower than that in CHX and EDTA plus NaOCl groups. Conclusion: Resil experimental sealer had a lower pushout bond strength than AH26.